Corporate Social Responsibility, Audit Committee, and Public Accounting Firm: Implications for Tax Aggressiveness in Financial Distress Situations - Aulia Agustini; Nanda Wahyu Indah Kirana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Taxes is a very influential sector supporting state revenue because most of the state revenue comes from tax revenue. Sources of tax in Indonesia come from individual taxpayers and corporate taxpayers. In its implementation, there are differences of interest between taxpayers and the government. Differences of interest cause taxpayers to tend to reduce the amount of tax payments, both legally and illegally. This study’s focus is to analyze whether Corporate Social Responsibility, Audit Committees, and Public Accounting Firms influence Tax Aggressiveness in Financial Distress conditions. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2023. This study uses a quantitative method with sampling using the purposive sampling method with a sample size of 53 companies with 6 years of observation. The data used in this study are secondary data taken from the company’s annual financial report. The analysis tool in this study uses Partial Least Squares (PLS). The results of this indicate that: Corporate Social Responsibility affects Tax Aggressiveness, The Audit Committee does not have an effect on Tax Aggressiveness, Public Accounting Firm does not affect Tax Aggressiveness, Financial Distress does not affect Tax Aggressiveness, Corporate Social Responsibility does not have an effect on Financial Distress, the Audit Committee does not affect Financial Distress, and Public Accounting Firm does not have an effect on Financial Distress.